Answer:
F(2x+3) = 12/(2x+3) +1/2
Explanation:
Put the argument of the function where the variable is. You can simplify if you want, but the original function definition is not simplified, so we assume it is not required.
F(x) = 12/x + 1/2
Put (2x+3) where x is:
F(2x+3) = 12/(2x+3) + 1/2
_____
Comment on the function
If you intend f(x) = 12/(x +1/2), then you would do the same thing: put (2x+3) where x is. In this case, you could combine the +3 and the +1/2, if you want.
... F(2x+3) = 12/((2x+3) +1/2) = 12/(2x +3.5)